1994
DOI: 10.1148/radiology.192.3.8058954
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic appearance of Chlamydia pneumoniae (TWAR strain) respiratory infections. CBPIS Study Group. Community-based Pneumonia Incidence Study.

Abstract: Different radiographic patterns exist for the two types of acute C pneumoniae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…In the present study, influenza virus type A and respiratory syncytial virus were the second and third most common copathogens, whereas, in the study of LIEBERMAN et al [22], they were M. pneumoniae and Legionella sp. MCCONNELL et al [23], in a study of 62 patients with C. pneumoniae pneumonia, divided the patients into those with primary infection (n=17) and those with recurrent infection (n=38). Seven (41%) with primary infection had a second respiratory pathogen present and seven (18%) in the recurrent infection group also had more than one respiratory pathogen present.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, influenza virus type A and respiratory syncytial virus were the second and third most common copathogens, whereas, in the study of LIEBERMAN et al [22], they were M. pneumoniae and Legionella sp. MCCONNELL et al [23], in a study of 62 patients with C. pneumoniae pneumonia, divided the patients into those with primary infection (n=17) and those with recurrent infection (n=38). Seven (41%) with primary infection had a second respiratory pathogen present and seven (18%) in the recurrent infection group also had more than one respiratory pathogen present.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on the radiological appearance of Chlamydial infection showed that homogeneous lobar or segmental shadows, and patchy ones were the common radiological abnormalities (12,13). Spreading of shadows within the same lung and also to the previously unaffected opposite lung have been seen in a few patients (12).…”
Section: T E R Re C O V E R (8) Our Patient Was Identified and Categmentioning
confidence: 98%
“…Spreading of shadows within the same lung and also to the previously unaffected opposite lung have been seen in a few patients (12). However, it has not been fully discussed, whether or not these radiological findings are simple deterioration or migration of shadows.…”
Section: T E R Re C O V E R (8) Our Patient Was Identified and Categmentioning
confidence: 99%
“…Such cases of severe pneumonia often appear as interstitial shadows and present as ARDS (9)(10)(11)(12). Notably, the occurrence of interstitial pneumonia is considered to be evidence of reinfection with this pathogen (13). It has been reported that the 60-kDa protein of C. pneumoniae represents an antigen for delayed-type hypersensitivity, the presumptive cause of interstitial pneumonia and ARDS (13).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the occurrence of interstitial pneumonia is considered to be evidence of reinfection with this pathogen (13). It has been reported that the 60-kDa protein of C. pneumoniae represents an antigen for delayed-type hypersensitivity, the presumptive cause of interstitial pneumonia and ARDS (13). In case 1, the nature of the antibody profile indicated a significant possibility of C. pneumoniae reinfection.…”
Section: Discussionmentioning
confidence: 99%